Genetic similarity among Dendrobium species from Indonesia using RAPD markers - SRI HARTATI; SAMANHUDI SAMANHUDI; ONGKO CAHYONO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Hartati S, Samanhudi, Cahyono O. 2023. Genetic similarity among Dendrobium species from Indonesia using RAPD markers. Biodiversitas 24: 5015-5021. Dendrobium genus orchids are one of the most popular commodities in the world due to their diverse range of flower sizes, shapes, and colors. To enhance plant breeding programs and genetic resources, it is necessary to obtain information on genetic similarity between orchids of the Dendrobium genus through molecular analysis techniques. Therefore, this study aimed to assess the genetic similarity among five Dendrobium species using molecular markers, specifically RAPD. The plant material used was obtained from five species of the Dendrobium spp, namely (i) Dendrobium mirbelianum; (ii) Dendrobium lamellatum, (iii) Dendrobium secundum, (iv) Dendrobium bracteosum, and (v) Dendrobium purpureum. The analysis was carried out to determine the genetic diversity of the Dendrobium orchids using RAPD markers. A total of five RAPD primers were used for amplification, namely OPD 8, OPA 7, OPA 13, OPB 12, and OPB 18. The scoring data were analyzed using NTSYS-pc (Numerical Taxonomy and Multivariate Analysis System) version 2.02 which produced data in the form of cluster dendrograms. The dendrogram that was constructed by Unweighted Pair Group Method Using Arithmetic Average (UPGMA) classified the five Dendrobium species into two main clusters. The results showed that there were two clusters, namely Cluster A consisting of D. mirbelianum, D. lamellatum, and D. secundum while Cluster B consisted of D. bracteosum and D. purpureum. Furthermore, the polymorphism of the five RAPD primers was very high, ranging from 91.6 to 100%, measuring 250-1900 bp. The coefficient of genetic similarity analyzed using the five RAPD primers ranged from 0.24 to 0.77. The species D. mirbelianum and D. lamellatum had a high coefficient of genetic similarity. Which can be discovered through parental selection in breeding program.